Effect of dialysis and transplantation on myocardial repolarization parameters and P‐wave dispersion in chronic kidney disease - Murat Akcay (Journal of Arrhythmia, 2021)
Abstract Background Chronic kidney disease (CKD) patients are at higher risk for cardiac arrhythmias. The risk of arrhythmia may change with different treatment modalities. We proposed to compare the effects of varied therapy methods on myocardial repolarization parameters (Tp‐e, QT, QTc intervals, Tp‐e/QT, Tp‐e/QTc ratios) and P‐wave dispersion (PWD) in patients with CKD. Methods Three groups were formed from the patients aged between 18 and 65 years, as Group 1 consisting of CKD patients receiving hemodialysis (HD) three times a week, Group 2 consisting of predialysis CKD patients and Group 3 consisting of CKD patients who underwent successful transplantation. All patients’ basic demographic data, risk factors, and echocardiographic parameters were recorded, and electrocardiographic repolarization parameters and PWD were analyzed. Results The PR, QT, and QTc intervals were significantly shorter in the transplantation group compared to the other groups (P = .020, P < .001, P = .035; respectively). Tp‐e interval, Tp‐e/QT, and Tp‐e/QTc ratios were significantly higher in the predialysis group compared to the other groups (P < .001, P < .001, P = .001; respectively), while there was no significant variation between the HD and transplantation groups (P > .05). PWD was significantly increased in the predialysis group compared to other two groups (P < .001), while no significant variation between the HD and transplantation groups was observed. Conclusion We found that the Tp‐e interval, Tp‐e/QT, Tp‐e/QTc, and PWD were significantly higher in the predialysis CKD group, but the PR, QT, and QTc intervals were significantly shorter in the transplantation group compared to the other groups. The prognostic significance and prediction of these parameters in arrhythmic events in CKD patients requires further evaluation with long‐time follow‐up.